2013
DOI: 10.1519/jpt.0b013e318264b5e8
|View full text |Cite
|
Sign up to set email alerts
|

The 6MWT

Abstract: There was good agreement between these distance measures for the 6MWT. The use of a pedometer was found to be a valid measure of walking distance during the 6MWT. It was also found that the method of instruction made no differences in walking distance. Although the change was minimal on the Borg scale, the RPE was found to be significantly different between far and fast trials in healthy adults. From this study, it appears that that either mode of instruction is valid in healthy community-dwelling populations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The 6MWT is known to be influenced by motivation (Southard and Gallagher, 2013 ). Every precaution has been taken by the researchers to standardize the administration of the test.…”
Section: Discussionmentioning
confidence: 99%
“…The 6MWT is known to be influenced by motivation (Southard and Gallagher, 2013 ). Every precaution has been taken by the researchers to standardize the administration of the test.…”
Section: Discussionmentioning
confidence: 99%
“…Use of assistive device was permitted during the testing since previous study reported that temporal gait variability in PwMS was not distinguished by usage of assistive device [ 14 ]. The participants were instructed to walk as fast as possible to cover as much distance as possible [ 20 ]. The 6MWT was conducted in a 21-meter hallway free of obstacles and distractions.…”
Section: Methodsmentioning
confidence: 99%
“…Various parameters of gait can be measured by clinicians during assessment. For example, clinicians can use a patient's gait speed [14,15], gait symmetry [16], gait endurance [17], adaptability of gait [18], and/or dual-task performance during gait [19, 20•] to quantify gait performance. Evidence on each of these parameters pertaining to older adults is presented below.…”
Section: Gait Assessmentsmentioning
confidence: 99%
“…(2013) conducted a study to determine how 6MWT distances compared between two different methods of measurement (pedometers versus measuring linear distance) and between two different methods of instruction ("walk as FAR as you can in six minutes" versus "walk as FAST as you can in six minutes" [17]). No differences were found between measurement or instruction methods [17] indicating that either method of measurement and/or instruction can be used clinically.…”
Section: Gait Endurancementioning
confidence: 99%
See 1 more Smart Citation